2021
DOI: 10.1002/jcop.22779
|View full text |Cite
|
Sign up to set email alerts
|

Internet use, depression, and cognitive outcomes among Chinese adolescents

Abstract: This study provides new evidence on how the growingly significant digital life shapes Chinese adolescents' cognitive and mental health outcomes based on their gender, parental education, and geographical location. Using the China Education Panel Survey, a nationally representative survey following 12-15-year-old students in 2013 and 2014, and individual fixed-effect models, we find that more time spent on the Internet is associated with higher selfreported depression scores. This negative impact on mental heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 60 publications
0
27
2
Order By: Relevance
“…Research on adolescents in developed countries suggests an inconsistent relationship between daily Internet use time and depression. Some studies support the displacement hypothesis, suggesting that daily Internet use time or frequency is positively associated with the risk of depression [15,33,34]. Some studies found a nonlinear U-shaped relationship [35, 36].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Research on adolescents in developed countries suggests an inconsistent relationship between daily Internet use time and depression. Some studies support the displacement hypothesis, suggesting that daily Internet use time or frequency is positively associated with the risk of depression [15,33,34]. Some studies found a nonlinear U-shaped relationship [35, 36].…”
Section: Discussionmentioning
confidence: 95%
“…Most studies on Internet use among Chinese adolescents used data from a time when only a minority of young people were online. They focused on Internet addictive behaviors or measured Internet use time as a continuous variable without observing the health effects of short durations or moderate use [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the rapid spread of the internet and digital devices, Zhou and Ding (2022) then investigated how the growingly significant digital life shapes Chinese adolescents' cognitive and mental health outcomes. They found that spending more time on the internet may increase the self-reported depression scores of teenagers, and such effects vary by students with different features.…”
Section: School/after-school Engagement and Child Developmentmentioning
confidence: 99%
“…Scholars have actively explored the decline in adolescent health [ 2 , 3 ], and reached a basic consensus that socio-environmental factors, rather than genetic (biological) factors, are at play. For example, some scholars discovered that socio-environmental factors are particularly important in a period of dramatic lifestyle changes and increasing risks to adolescent health levels [ 4 ]. Although a number of studies have examined the effects of physical activity, screen time, and academic burden on adolescent health [ 5 , 6 , 7 ], few studies have been conducted on Chinese samples.…”
Section: Introductionmentioning
confidence: 99%